Sport and physical activity for mental health - Carless, David, 1970-; Douglas, Kitrina (Chichester : Wiley-Blackwell, 2010)
'PRIMARY * Mental Health Nurses * Occupational Therapists working in mental health * Physiotherapists working in mental health * Psychotherapists * Occupational Health practitioners SECONDARY * Social Workers * Psychiatrists * Clinical Psychologists * Undergraduate and Postgraduate students of mental health nursing, occupational therapy, occupational health, physiotherapy, social work, mental health, psychiatry, psychotherapy and sport and exercise science'--Provided by publisher
Includes bibliographical references (p. [166]-175) and index
Keywords: Mental disorders -- Rehabilitation; Exercise -- Psychology; Exercise Therapy -- methods; Occupational therapy -- methods; Sports -- psychology